2022
DOI: 10.1001/jamainternmed.2022.4268
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antidepressant Use During Pregnancy With Risk of Neurodevelopmental Disorders in Children

Abstract: ImportanceAntidepressant use during pregnancy has been associated with neurodevelopmental disorders in children in some studies. However, results may be explained by uncontrolled confounding by parental mental health status, genetics, and environmental factors.ObjectiveTo evaluate the association between antidepressant use in pregnancy and neurodevelopmental outcomes in children.Design, Setting, and ParticipantsThis cohort study of health care utilization data was separated into cohorts of publicly and private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…It is worth noting that the reported rates of neurodevelopmental disorders in children in the study, even in the unexposed groups, were 30% and 15% 1. Although one estimate has suggested that the prevalence of neurodevelopmental impairments and conditions is around 3%–4% of children in England, it is difficult to find directly comparable data 2…”
Section: Contextmentioning
confidence: 76%
See 4 more Smart Citations
“…It is worth noting that the reported rates of neurodevelopmental disorders in children in the study, even in the unexposed groups, were 30% and 15% 1. Although one estimate has suggested that the prevalence of neurodevelopmental impairments and conditions is around 3%–4% of children in England, it is difficult to find directly comparable data 2…”
Section: Contextmentioning
confidence: 76%
“…This US cohort study investigated the association between antidepressant use during pregnancy with the risk of neurodevelopmental disorders in children 1. Pregnancy cohorts were identified from Medicaid healthcare records from 2000 to 2014, and private health insurance claims from 2003 to 2015.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations